The Role of Peasant, Common Man, and Working Class in the National Movement during the Colonial Period: North Karnataka - Pirajade Mahmadaslam, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The colonial period in North Karnataka witnessed a dynamic interplay between elite nationalist politics and grassroots social forces-peasants, commoners, and the working class-whose collective actions shaped the region’s contribution to India’s freedom struggle. Drawing from secondary literature, gazetteers, and colonial records, this paper examines how agrarian distress, indebtedness, and early industrial developments spurred localized mobilizations that later converged with national movements. Peasant resistance ranged from tax defaults to active participation in Non-Cooperation, Civil Disobedience, and Quit India campaigns. Artisans and small traders functioned as intermediaries linking urban and rural spheres, while the emerging working class in Belgaum, Hubli, and Dharwad adopted strike tactics connecting economic justice with anti-imperialist demands. Using a subaltern perspective, this study argues that North Karnataka’s nationalist trajectory cannot be understood without recognizing these non-elite actors whose collective defiance eroded colonial legitimacy and expanded the social base of India’s struggle for independence.
Keywords: Peasants; Working Class; North Karnataka; National Movement